The effect of sustainable development on environment agendas. Case study: Putrajaya green city - Muhammad Aqmarul Azri, Azmi (2015)
During the past four decades, the relationships between the evolution of development strategies and environmental concerns within the urban context. Urbanization increases the pressure on limited resources and available services, and threatens health, the environment and urban productivity. This study is a descriptive study that more emphasis to the elaboration of an issue of concern and interest in relation to the implementation of the Green City Program in Putrajaya. This study will use a qualitative study and it will rely on analytical approach. The data will collected from research report, government report, scientific article and from others reliable sources. Nowadays, as a result of this development, studies about the aspects of sustainable development are increasing. Sustainable development is popularly described as “a development that meets the needs of the present without compromising the ability of the future generations to meet their own needs” (WCED, 1987 in Moffat, 1996). Malaysia is actively engaged in international pacts concerning sustainable development efforts. As a result, the Malaysian Government’s sustainability agenda has prioritized the balance between socio-economic and ecological systems to avoid further environmental damage